{μ-6,6′-Dimethoxy-2,2′-[butane-1,4-diylbis(nitrilomethylidyne)]diphenolato-1:2κ8O6,O1,O1′,O6′:O1,N,N′,O1′}tris(nitrato-1κ2O,O′)copper(II)gadolinium(III) - Christopher Chan; Xiaoping Yang; Richard A. Jones; Bradley J. Holliday; Julie M. Stanley (Acta Crystallographica Section E, 2010)
In the title dinuclear complex, [CuGd(C20H22N2O4)(NO3)3], the CuII ion is located in the inner N2O2 cavity of the Schiff base ligand and adopts a distorted square-planar geometry. The GdIII ion is ten-coordinate being bound to ten O atoms, four from the Schiff base ligand and six from three bidentate nitrate anions. The CuII and GdIII ions are linked by two phenolate O atoms of the Schiff base ligand, with a separation of 3.5185 (9) Å.